RIPENSARE LA SCUOLA COME LUOGO PRIVILEGIATO DI EDUCAZIONE - Indellicato, Rosa (Civitas et Lex, 2019)
The emerging educational question is at the center of a lively cultural debate that revolves around important questions: what is the role of the school in post-modern society? What is the goal of education in the time of globalization? The answer can only be articulated considering the profound transformations that are connoting advanced modernity, in which more and more different conceptions of education and formation coexist, also due to the multicultural and multiethnic character of our society at the beginning of the third millennium. At this point it must be strongly emphasized that a good education moves from a "holistic" anthropological perspective, where they simultaneously find equilibrium between homo rationalis and homo senties. A model of education united by two perspectives: an emotional thinking and an intelligent feeling.